Mapping the Progressive Treatment-Related Reduction of Active MRI Lesions in Multiple Sclerosis - Giorgio, Antonio; Battaglini, Marco; Gentile, Giordano; Stromillo, Maria Laura; Gasperini, Claudio; Visconti, Andrea; Paolillo, Andrea; De Stefano, Nicola (Frontiers in Neurology, 2020)
Objective: To assess treatment-related spatio-temporal dynamics of active MRI lesions in relapsing-remitting multiple sclerosis (RRMS) patients. Methods. We performed a post-hoc analysis of MRI data acquired at weeks 4, 8, 12 and 16, in RRMS patients from the multicenter randomized IMPROVE study, which compares patients treated with subcutaneous interferon β-1a 44 mcg three times weekly (n=120) versus placebo (n=60). We created lesion probability maps (LPMs) of the cumulative combined unique active (CUA) lesions in each patient group at each time point. Group differences were tested in terms of lesion spatial distribution and frequency of occurrence. Results. Spatial distribution of CUA lesions throughout the study was less widespread in the treated than placebo group, with a 50% lower lesion accrual (24 vs 48 cm3/month). Similar results were obtained with the WM tract analysis, with a reduction ranging from -47% to -66% in the treated group (p<0.001). On voxelwise analysis, CUA lesion frequency was lower in the treated than placebo group at week 4 (p=0.07, corrected), becoming particularly pronounced (p≤0.03, corrected) from week 8 onwards in large clusters of WM tracts, with peaks along fronto-parietal parts of corticospinal tract, thalamic radiation, and superior longitudinal fascicle. Conclusion. LPM showed that, in the short term, treatment-related reduction of MRI lesion activity in RRMS patients in specific, clinically relevant brain locations. Such quantitative approach might be a promising additional endpoint in future MS studies alongside number and volume of WM lesions. Trial registration: ClinicalTrials.gov identifier NCT00441103